Analisis Pemahaman dan Penggunaan Bahasa Indonesia Ilmiah dalam Ranah Perguruan Tinggi - Cut Monika Tari; Diva Nabila Chairani S; Winku Elvha Aripaga; Muhammad Surip (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Indonesian language, as the national language, plays a crucial role in higher education, serving not only as a means of communication but also as a vehicle for the development of scientific knowledge. However, the understanding and usage of academic Indonesian in universities remain challenging. This study analyzes the comprehension and utilization of academic Indonesian at the Universitas Negeri Medan by both students and lecturers. The research methodology employs a qualitative approach with a literature review technique. Findings reveal that the usage of Indonesian still falls short of linguistic standards, particularly in formal academic contexts. Factors such as a lack of reading interest, inadequate awareness of the importance of academic Indonesian, and the predominance of foreign language usage impact the comprehension and application of academic Indonesian. Therefore, efforts are required to enhance the understanding and usage of academic Indonesian, including through mentoring, training, and increasing awareness of the significance of proper national language usage.